The Effect of Centrifugation Time on Sexing Spermatozoa with Bovine Serum Albumin Media on the Morphology of X-Y Spermatozoa in Simmental Cattle - Langgeng Priyanto; R. Riswandi; Oktora Dwi Putranti; Muhammad Gunawan; Apriansyah Susanda; Khusnul Khotimah (Chalaza Journal of Animal Husbandry, 2022)
Sexing and centrifugation of spermatozoa is one way to improve the quality of spermatozoa. This study aimed to obtain the right centrifugation time for sexing spermatozoa with Bovine Serum Albumin media on the morphology of X-Y spermatozoa in Simmental cattle. This study was carried out from October 2021 to November 2021 at the Laboratory of Animal Reproduction and Health at the Breeding Center for Superior Livestock and Forage, Sembawa. The design used in this study was a completely randomized design (CRD) with 3 treatments and 4 replications. Centrifugation treatments for sexing spermatozoa with BSA media P1: centrifugation time 4 minutes, P2: centrifugation time 8 minutes, and P3: centrifugation time 12 minutes. The parameters observed were the morphology of the X and Y spermatozoa. The results showed that the centrifugation time for sexing spermatozoa—which was different with Bovine Serum Albumin (BSA) media—indicates that the X spermatozoa abnormalities had no significant effect (P0.05) but the Y spermatozoa abnormalities had a significant effect (P0.05). The result of the right time use was in the P1 treatment with a centrifugation time of 4 minutes where the abnormalities value in the lower layer Y was 28.79%.